The Children of Looked After Children Outcomes, Experiences and Ensuring Meaningful Support to Young Parents In and Leaving Care - Roberts, Louise (2021)
Based on groundbreaking original research, this book provides a comprehensive account of the issues surrounding pregnancy and parenthood for young people in and leaving care. Featuring the voices of care-experienced parents, together with reflections from practitioners, it offers valuable insights into the issues facing this group. Using qualitative data to explore why parenthood is such an important issue for young people in and leaving care, this book shows what can be learned from their experiences in order to improve outcomes for parents and children in the future. The author highlights the practical and emotional needs of care-experienced parents and gives clear advice for practitioners on how these needs might be better addressed through summary points, practice guidance and recommendations for policy and practice.